Investigating intermolecular interactions motifs in ammonium carboxylate salts - Odendal, James Arthur (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2009.